The influence of role models on young adults purchase - Ernest Cyril, de Run; Muhammad Mohsin, Butt; Chung, Yen Nee (Jurnal Kemanusiaan, 2010)
This study explores the influence of direct (parents) and vicarious (celebrities) role models on young consumer’s purchase intention and behavior in Malaysia. The study partially replicates previous studies conducted in the west while exploring the eastern perspective. The data was collected using convenience sampling. Respondents were mostly undergraduate students at a public university in Sarawak, Malaysia. They were asked to respond to a structured questionnaire which was based on previous studies conducted in the same area. Regression analysis was carried out to estimate the impact of role model influence on purchase intention and behavior. The results indicate that both direct and vicarious role model significantly influence purchase intention. However finding do suggests that the direct role model does not influence purchasing behavior. This study significantly contributes in understanding the role model influence on ever growing youth market in Malaysia.